Construcción de comunidades profesionales centradas en la inclusión: personal inspector, docente y asesor en el proyecto Erasmus+ “Incluídas” - Eizaguirre Santillan, Alicia; Latas Calvo, Román; Pastoriza Espasandín, Diana; García Liñares, Sergio (Avances en Supervisión Educativa, 2026)
The article analyses the Erasmus+ accreditation project (KA120SCH) “Incluídas”, coordinated by the Centro Autonómico de Formación e Innovación (Galicia) and funded under the Erasmus+ KA1 programme (2023-1-ES01-KA120-SCH-000185740), as an internationalisation experience aimed at improving inclusive education and fostering shared professional development. Based on co-design, joint training, the use of digital portfolios, and observation in European contexts, the project brings together inspectors, teachers and advisors, promoting dynamics of distributed leadership. From a comparative perspective, the article examines contributions from different education systems —particularly the Portuguese one— in areas such as pedagogical leadership, governance, teacher training and attention to diversity, as well as the evolution of the role of inspection towards functions of support and improvement. The results, although still incipient, show a progressive development of a shared vision of inclusion, fostering participants’ empowerment and the consolidation of a professional community.
Keywords: internationalization, inclusion, distributed leadership, co-design, joint training, professional development, observation, professional community, digital portfolios.